1977
DOI: 10.1210/endo-101-1-32
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peptide Anabolic Hormones on Growth of Myoblasts in Culture

Abstract: The roles of growth hormone and somatomedin in stimulating muscle cell proliferation were investigated in a series of experiments on myoblast growth in culture. At levels 100 times normal circulating concentrations, neither growth hormone nor insulin stimulated growth of rat muscle cells in serum-free medium. In contrast, Temin's Multiplication Stimulating Activity (MSA), a close biological and chemical analog which served as a somatomedin surrogate in this study, was active at concentrations corresponding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…We also showed that MSA stimulated both L6 proliferation (Florini et al, 1977;Florini and Ewton, 1981) and differentiation as measured by increased fusion and elevated CK activity. In an attempt to establish more clearly any relationship between these observations, we measured the time course of changes in ODC levels as myotubes formed.…”
Section: Time Course Of Odc and Ck During Msa-stimulatedmentioning
confidence: 55%
“…We also showed that MSA stimulated both L6 proliferation (Florini et al, 1977;Florini and Ewton, 1981) and differentiation as measured by increased fusion and elevated CK activity. In an attempt to establish more clearly any relationship between these observations, we measured the time course of changes in ODC levels as myotubes formed.…”
Section: Time Course Of Odc and Ck During Msa-stimulatedmentioning
confidence: 55%
“…FIGURE 6 Gel filtration chromatography of medium on Sephacryl S-200. Medium that had been exposed to fibroblast cultures for 24 FIGuRE 7 Gel filtration chromatography of medium on Sephadex G-50.…”
Section: Resultsmentioning
confidence: 99%
“…Since immunoreactive somatomedin production may be a rate-limiting factor for fibroblast growth, the delineation of the hormonal control of somatomedin production should lead to a better understanding of the mechanisms controlling human fibroblast growth. INTRODUCTION The somatomedins, a family of growth hormonedependent, insulinlike peptide growth factors, have been shown to be mitogenic for a variety of types of cultured cells (1)(2)(3)(4)(5)(6). Cartilage from various species and fibroblasts derived from chick (7) and mouse (8) embryos fail to synthesize DNA or undergo mitosis normally when incubated in somatomedin-deficient serum.…”
mentioning
confidence: 99%
“…Although in vitro data are conflicting with regard to the direct anabolic properties of GH (6-8) and suggest that many of the biological activities of this hormone may be mediated by secondary mediators such as insulin-like growth factors (IGFs) (7)(8)(9), it is clear that administration of this peptide to animals (10) and humans (11) promotes weight gain and whole body nitrogen retention. However, a mechanistic analysis of these effects in humans has previously been limited partly by the restricted quantities of the hormone and by possible contaminants in pituitary extracts of this hormone (12).…”
Section: Introductionmentioning
confidence: 99%